Effects of Bleaching Associated with Er:YAG and Nd:YAG Laser on Enamel Structure and Bacterial Biofilm Formation. (20th December 2021) - Hou, Xiuxiu; Yuan, Keyong; Huang, Zhengwei; Ma, Rui
Abstract : Objective . To compare the effects of bleaching associated with Er:YAG and Nd:YAG laser on enamel structure and mixed biofilm formation on teeth surfaces. Materials and Methods . Sixty-eight enamel samples were randomly divided into four groups (n = 17 ), control, Opalescence Boost only, Opalescence Boost plus Er: YAG laser, and Opalescence Boost plus Nd:YAG laser. The structure was observed using SEM after bleaching. Subsequently, the treated enamel samples were also cultured in suspensions of Streptococcus mutans, Streptococcus sanguis, Actinomyces viscosus, and Fusobacterium nucleatum ( Fn ) for 24 and 48 h. Biofilm formation was quantified by crystal violet staining, and the structure was visualized by confocal laser scanning microscopy. The data were analyzed using the Kruskal-Wallis method. Results . The enamel structure significantly changed after bleaching. There was no obvious difference in the biofilm formation after 24 h; however, after 48 hours, the amount of biofilm increased significantly. Remarkably, the amount was significantly higher on enamel bleached only, however, there was no significant difference between samples bleached with Er:YAG or Nd:YAG laser compared to the control. Conclusions . Bleaching only appeared to markedly promote biofilm formation after 48 h, and the biofilms on samples bleached with Er:YAG or Nd:YAG laser did not change significantly, showing that bleaching with Er:YAG or Nd:YAG laser can be safely applied in clinical practice.